Direct oxidation of amines to nitriles in the presence of ruthenium-terpyridyl complex immobilized on ILs/SILP1. Issue 5 (28th May 2015) - Pavel, Octavian Dumitru; Goodrich, Peter; Cristian, Liliana; Coman, Simona M.; Pârvulescu, Vasile I.; Hardacre, Christopher
<x xml:space="preserve">Abstract</x> Ru2Cl4(az-tpy)2 was immobilized within a range of supported ionic liquids on silica. SILP operates as an efficient heterogeneous catalyst in oxidation of long chain linear primary amines to corresponding nitriles.